2018
DOI: 10.1021/acsami.8b09084
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Light Absorption by GaN Truncated Nanocones for High Performance Water Splitting Applications

Abstract: Despite the importance of gallium nitride (GaN) nanostructures for photocatalytic activity, relatively little attention has been paid to their geometrical optimization on the basis of wave optics. In this study, we present GaN truncated nanocones to provide a strategy for improving solar water splitting efficiencies, compared to the efficiency provided by the conventional geometries (i.e., flat surface, cylindrical, and cone shapes). Computational results with a finite difference time domain (FDTD) method and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 38 publications
0
39
0
Order By: Relevance
“…6). 42 The study theoretically and experimentally revealed that the truncated cone is the most appropriate for light trapping on the nanostructure close to the electrolyte reducing the path of photo-generated charges, in other words, a fast charge transport, and consequently showed an increase in the photocurrent. Furthermore, thermally dewetted metal particles for top-down structuring of a PEC cell with a truncated cone shape is a controllable and non-lithographical approach and thus, can reduce the fabrication cost.…”
Section: Chemical Vapor Depositionmentioning
confidence: 95%
See 1 more Smart Citation
“…6). 42 The study theoretically and experimentally revealed that the truncated cone is the most appropriate for light trapping on the nanostructure close to the electrolyte reducing the path of photo-generated charges, in other words, a fast charge transport, and consequently showed an increase in the photocurrent. Furthermore, thermally dewetted metal particles for top-down structuring of a PEC cell with a truncated cone shape is a controllable and non-lithographical approach and thus, can reduce the fabrication cost.…”
Section: Chemical Vapor Depositionmentioning
confidence: 95%
“…This can be resolved by enhancing the STH efficiency and using nano-structures in PEC cells that are suitable for water splitting which could be an alternative route. 42 As briey mentioned in the PVD section, structuring the PEC cell can enhance light absorption and surface reactions thereby can possibly increase the STH efficiency. 30 However, the method addressed in ref.…”
Section: Chemical Vapor Depositionmentioning
confidence: 99%
“…The device also achieved high values of photocurrent of 0.32 mA/cm 2 by using etching voltages at 10 V (Figure 5e). Kim et al had prepared GaN truncated nanocones [76], which was shown in Figure 5c. GaN truncated nanocones have concentrated incident light inside the nanostructure and enhanced the light trapping with reduced light losses from surface reflection.…”
Section: Gan Materials Having Different Morphologiesmentioning
confidence: 99%
“…Anti-reflection coatings (ARCs) have been extensively studied in optoelectronics for efficient light management, such as in light-emitting diodes and solar cells exploiting the aforementioned functions. [7][8][9]. Numerous manufacturing processes have been developed with the increasing demand for ARCs.…”
Section: Introductionmentioning
confidence: 99%